Pengaruh E-Wom dan E-Servqual Terhadap Keputusan Pembelian Makanan pada Grabfood di Kota Palembang - Siti Soeleha; Yulia Hamdaini Putri; Aslamia Rosa (UNIVERSITAS MARITIM AMNI SEMARANG, 2025)
The purpose of this study is to examine the influence of E-WOM and E-Servqual on food purchase decisions on GrabFood in Palembang. This study is categorized as quantitative research. The respondents in this study are users who have purchased and used the GrabFood application. The sample for this study consists of about 100 respondents and uses purposive sampling method along with non-probability sampling techniques. The instrument for collecting data for this study is a questionnaire analysis evaluated using a Likert scale and linear regression analysis techniques. The results of this study indicate that the t-test variables e-wom and e-servqual have a significant and partial effect on purchasing decisions. The results of the study on the f-test variables e-wom and e-servqual have a positive and significant influence on purchasing decisions simultaneously.